Differential Effects of Fibroblast Growth Factors on Expression of Genes of the Plasminogen Activator and Insulin-like Growth Factor Systems by Human Breast Fibroblasts - Sieuwerts, Anieta M.; Martens, John W. M.; Dorssers, Lambert C. J.; Klijn, Jan G. M.; Foekens, John A. (Thrombosis and Haemostasis, 2002)
In breast stroma urokinase plasminogen activator (uPA) is predominantly expressed by fibroblasts located in the near vicinity of tumor cells, and fibroblast-derived insulin-like growth factor-1 (IGF-1) may be involved in inhibiting the expression of uPA in these fibroblasts. To investigate a possible role for fibroblast growth factors (FGFs), we evaluated the expression of components of the PA system and the IGF system in normal and tumor-tissue-derived human breast fibroblasts exposed to various FGFs in vitro. mRNA analysis revealed that FGF-1, FGF-2 and FGF-4 induced the mRNA expression levels of uPA, tPA, uPAR, PAI-1 and PAI-2, and reduced those of IGF-1, IGF-1R, IGF-2R and IGFBP-4, without significantly affecting the levels of IGFBP-3, IGFBP-5 and IGFBP-6 mRNA. Concerning the expression of IGF-2 mRNA, the effects mediated by FGF-1, FGF-2 and FGF-4 were divergent. In general, the effects elicited by FGF-1 on the various mRNA levels studied were rapid and short-term. Those mediated by FGF-2 overall lagged behind but were longer-lasting. For FGF-4 an in between pattern was observed. Blocking transcription and translation demonstrated that a) both the FGF-1 and FGF-2 induced effects were the result of altered gene transcription or mRNA stability, b) the short-term effects mediated by FGF-1 and FGF-2 required de novo protein synthesis, and c) the long-term effects elicited by FGF-2 did not depend on de novo protein synthesis during the first 24 h, but were triggered by proteins produced or made available thereafter. The data presented propose that of the FGFs studied (FGF-1, -2, -4, -5, and -7), FGF-2 is the most attractive target for therapeutical strategies aimed at diminishing the contribution of stromal fibroblasts in the PA-directed breast tumor proteolysis.
Keywords: Fibroblast growth factors; plasminogen activator system; insulinlike growth factor system; fibroblasts; human breast cancer